1993
DOI: 10.1159/000282536
|View full text |Cite
|
Sign up to set email alerts
|

Papillary Renal Cell Carcinoma Associated with Autosomal Dominant Polycystic Kidney Disease

Abstract: A case of papillary renal cell carcinoma in a patient suffering from autosomal dominant polycystic kidney disease is described. The occurrence of papillary renal cell carcinoma in polycystic kidneys in the literature is reviewed and the implications of operative management and further surveillance in case of a papillary renal cell carcinoma are discussed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
8
0
2

Year Published

1996
1996
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 7 publications
0
8
0
2
Order By: Relevance
“…In fact, the association of ADPKD with renal-cell cancer is rare. Only some 60 cases have been reported, which sug gests that the incidence in ADPKD does not exceed that in the normal population [20,21].…”
Section: Discussionmentioning
confidence: 97%
“…In fact, the association of ADPKD with renal-cell cancer is rare. Only some 60 cases have been reported, which sug gests that the incidence in ADPKD does not exceed that in the normal population [20,21].…”
Section: Discussionmentioning
confidence: 97%
“…Of 44 patients, they also reported that 9 cases (20%) were PRCC as in our present cases, significantly higher than that of the general population (12%) ( Table I). Among these cases, five were type 1 and three weretype 2 [3][4][5]. However, it is also true that ESRD developed into multiple RCC much more often compared to sporadic RCC: 1.6% to 8.0% of the patients with ESRD, of whom 23% to 58% of the patients had acquired cystic disease of kidney (ACDK) [7].…”
Section: Discussionmentioning
confidence: 99%
“…To our knowledge, only 54 cases of RCC arising in patients with ADPKD have been reported 1-13. The association between RCC and chronic renal failure in patients with ADPKD remains controversial.…”
Section: Discussionmentioning
confidence: 99%
“…In these cases, clear cell RCC was the most common histological subtype (48%), followed by papillary RCC (14%) 1-13. There were only two cases with the coexistence of different histological subtypes of RCC 3,5.…”
mentioning
confidence: 96%